Functional tumor-derived exosomes in NSCLC progression and clinical implications - Gao, Yuxin; Xie, Jun; Yang, Zhenya; Li, Mengxi; Yuan, Hongfan; Li, Rui (Frontiers in Pharmacology, 2025)
Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancer cases and remains one of the leading causes of cancer-related mortality worldwide. The high mortality rate is primarily driven by delayed diagnosis, rapid metastasis, and frequent recurrence. Tumor-derived exosomes (TEXs) have emerged as critical mediators in NSCLC progression, offering valuable insights into the tumor microenvironment. Exosomes are small membrane vesicles that facilitate intercellular communication and transport bioactive molecules, including proteins, RNAs, and DNAs, thereby reflecting the genetic complexity of tumors. These exosomes play a key role in promoting tumor metastasis, epithelial-mesenchymal transition (EMT), neovascularization, drug resistance, and immune evasion, all of which are pivotal in the development of NSCLC. This review explores the diverse roles of TEXs in NSCLC progression, focusing on their involvement in pre-metastatic niche formation, tissue metastasis, and immune modulation. Specifically, we discuss the roles of exosome-associated RNAs and proteins in NSCLC, and their contribute to tumor growth and metastasis. Furthermore, we explore the potential of TEXs as biomarkers for NSCLC, emphasizing their application in diagnosis, prognosis, and prediction of resistance to targeted therapies and immunotherapies.